PENGARUH BRAND LUXURY TERHADAP BRAND ATTITUDE, TRUST, E-WOM MELALUI CUSTOMER SATISFACTION - Yulianzha, Tiara Andra; Tuti, Meylani (Human Capital Development, 2024)
This research investigates the impact of brand luxury variables on brand attitude, trust, and E-women through customer satisfaction with the Somethinc brand. 141 respondents who had purchased or used Somethinc products were included in this study. Accidental sampling techniques were employed to capture data through online questionnaires, which were subsequently processed using SmartPLS. The study's findings suggest that brand luxury substantially impacts brand attitude, trust, EWOM, and consumer satisfaction. Brand attitude, trust, EWOM, and customer satisfaction are all influenced by the brand's prestige. Additionally, brand attitude influences trust, which in turn influences EWOM and consumer satisfaction. This demonstrates that consumers prioritize brand prestige